Detection of breast cancer cells in blood samples by immunostaining of the Thomsen–Friedenreich antigen. (May 2013) - Andergassen, Ulrich; Zebisch, Michael; Kölbl, Alexandra C; Schindlbeck, Christian; Ilmer, Matthias; Hutter, Stefan; Heublein, Sabine; Rack, Brigitte; Friese, Klaus; Jeschke, Udo
Aim: Disseminated tumor cells are found in the bone marrow of patients with epithelial carcinoma and are correlated with a poor prognosis of the disease. Their detection is a technical challenge. This report describes a model system for the detection of cancer cells by co-immunostaining of Thomsen–Friedenreich and Her-2 antigens.Methods & results: Small numbers of cancer cells from different cancer cell lines were mixed with blood samples of healthy donors. Cytospins were prepared and double immunostaining against Thomsen–Friedenreich antigen and Her-2 was carried out by fluorochrome-coupled antibodies. Quantification of Thomsen–Friedenreich and/or Her-2-positive cells was performed with an epifluorescence microscope. On average, 83% of cancer cells were recovered by this method.Conclusion: Immunostaining is a useful method for the detection of cancer cells in blood samples. Results of this model system will be transferred to bone marrow patient samples to prove the benefits for detection of disseminated tumor cells.